Deep brain stimulation in essential tremor: targets, technology, and a comprehensive review of clinical outcomes. (2nd April 2020) - Wong, Joshua K.; Hess, Christopher W.; Almeida, Leonardo; Middlebrooks, Erik H.; Christou, Evangelos A.; Patrick, Erin E.; Shukla, Aparna Wagle; Foote, Kelly D.; Okun, Michael S.
ABSTRACT: Introduction : Essential tremor (ET) is a common movement disorder with an estimated prevalence of 0.9% worldwide. Deep brain stimulation (DBS) is an established therapy for medication refractory and debilitating tremor. With the arrival of next generation technology, the implementation and delivery of DBS has been rapidly evolving. This review will highlight the current applications and constraints for DBS in ET. Areas covered : The mechanism of action, targets for neuromodulation, next generation guidance techniques, symptom-specific applications, and long-term efficacy will be reviewed. Expert opinion : The posterior subthalamic area and zona incerta are alternative targets to thalamic DBS in ET. However, they may be associated with additional stimulation-induced side effects. Novel stimulation paradigms and segmented electrodes provide innovative approaches to DBS programming and stimulation-induced side effects.